Ski touring: Analyzing risk-taking behavior and risk avoidance associated with an emerging outdoor activity in the Alps - Elisabeth Happ; Ursula Scholl-Grissemann; Martin Schnitzer (Elsevier, 2023)
Ski touring is an emerging trend in the Alps, defined as ascending and descending a slope/backcountry with ski-touring equipment. The aim of this research is to understand risk-taking behavior, risk-avoidance behavior and assessed expertise (ascending/descending) of backcountry ski tourers. A cross-sectional survey design was chosen (N ​= ​300). Results show that e.g. genderwise, the difference is statistically significant in terms of 'I consciously expose myself to danger' t(158) ​= ​2.94, and e.g. skillwise, for 'I check every piece of equipment before use' t(152) ​= ​−2.98 - providing insights into the risk behavior of BCSTers in terms of gender and skills.